Clinical utility of a blood-based EGFR mutation test in patients receiving first-line erlotinib therapy in the ENSURE, FASTACT-2, and ASPIRATION studies. (December 2018) - Wu, Yi-Long; Lee, Victor; Liam, Chong-Kin; Lu, Shun; Park, Keunchil; Srimuninnimit, Vichien; Wang, Jie; Zhou, Caicun; Appius, Anita; Button, Peter; Hooper, Gregory; Palma, John F.; et al.
Highlights: The cobas ® v2 EGFR mutation blood test has high specificity and good sensitivity. Sensitivity of the test was greatest in patients with larger baseline tumor burden. Prolonged survival was seen with discordant (tissue+/plasma-) EGFR mutation status. EGFR mutation testing in blood is a convenient, non-invasive, diagnostic option. These results inform the clinical utility of the cobas ® v2 EGFR mutation test. Abstract: Objective: Patients with advanced non-small-cell lung cancer (NSCLC) with an adenocarcinoma component are recommended to undergo epidermal growth factor receptor ( EGFR ) mutation testing when being considered for EGFR targeted therapy. We conducted an exploratory analysis to inform the clinical utility of EGFR mutation testing in blood cell-free DNA using thecobas ® EGFR Mutation Test v2. Materials and methods: Two EGFR mutation tests, a tissue-based assay (cobas ® v1) and a tissue- and blood-based assay (cobas ® v2) were used to analyze matched biopsy and blood samples (897 paired samples) from three Asian studies of first-line erlotinib with similar intent-to-treat populations. ENSURE was a phase III comparison of erlotinib and gemcitabine/platinum, FASTACT-2 was a phase III study of gemcitabine/platinum plus erlotinib or placebo, and ASPIRATION was a single-arm phase II study of erlotinib. Agreement statistics were evaluated, based on sensitivity and specificity between the two assays in subgroups of patients with increasing tumor burden. Results: Patients with discordant EGFR (tissue+/plasma-) mutation status achieved longer progression-free and overall survival than those with concordant (tissue+/plasma+) mutation status. Tumor burden was significantly greater in patients with concordant versus discordant mutations. Pooled analyses of data from the three studies showed a sensitivity of 72.1% (95% confidence interval [CI] 67.8–76.1) and a specificity of 97.9% (95% CI 96.0–99.0) for blood-based testing; sensitivity was greatest in patients with larger baseline tumors. Conclusions: Blood-based EGFR mutation testing demonstrated high specificity and good sensitivity, and offers a convenient and easily accessible diagnostic method to complement tissue-based tests. Patients with a discordant mutation status in plasma and tissue, had improved survival outcomes compared with those with a concordant mutation status, which may be due to their lower tumor burden. These data help to inform the clinical utility of this blood-based assay for the detection of EGFR mutations.